2014
DOI: 10.1039/c3cc45901b
|View full text |Cite
|
Sign up to set email alerts
|

New insights into carbon dioxide interactions with benzimidazole-linked polymers

Abstract: A synergistic experimental and theoretical study (DFT) highlights the impact of material design at the molecular and electronic levels on the binding affinity and interaction sites of CO2 with benzimidazole-linked polymers (BILPs); CO2 is stabilized by benzimidazole units through Lewis acid-base (N···CO2) and aryl C-H···O=C=O interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 19 publications
6
54
0
Order By: Relevance
“…However, the polymer P(PIOH-IPI) has a sharp weight loss around 100 °C, which can be attributed to the presence of water molecules coordinated to the OH-sites in the polymer chain. This assumption was supported by the elemental analysis results, which indicated the coordination of at least two water molecules to the polymer chain [22,23].…”
Section: Results and Discussion Synthesis And Characterization And Physupporting
confidence: 67%
“…However, the polymer P(PIOH-IPI) has a sharp weight loss around 100 °C, which can be attributed to the presence of water molecules coordinated to the OH-sites in the polymer chain. This assumption was supported by the elemental analysis results, which indicated the coordination of at least two water molecules to the polymer chain [22,23].…”
Section: Results and Discussion Synthesis And Characterization And Physupporting
confidence: 67%
“…Moreover, in the same study when different gases are compared, similar behavior is also observed on the binding energy vs sorption performance relation. In a different study again by Altarawneh, Q st for CO 2 was calculated via virial method and compared with the estimated binding energies via DFT calculations. Authors reported on the Q st as it has the highest value at zero coverage then start to drop as the sorption continues.…”
Section: Resultsmentioning
confidence: 99%
“…The binding affinity of CO 2 to the azo group was compared to the affinity for N 2 to the azo group using an azobenzene model. Electrostatic interactions between the N of the ring and the CO 2 molecule were designated as dipole-quadrupole and dipole-induced dipole interactions (Vogiatzis et al, 2009;Altarawneh et al, 2014).…”
Section: Cofs Which Utilize Channel Wall Functionalization For Increamentioning
confidence: 99%